Research of platform identity attestation based on trusted chip - Qian-ying ZHANG; Deng-guo FENG; Shi-jun ZHAO (Tongxin xuebao)
By studying the platform identity attestation base on trusted third parties, a scheme where a trusted computing platform is identified by a certificate and a token is proposed. In this scheme, only the token is used when the platform proves its identity. Compared to other schemes, this scheme not only has much lower calculation and communication, but also convinces the verifier of the trustworthiness of the client's platform state during the platform identity attestation. A detailed security proof of the proposed scheme is presented by using the protocol composition logic, and the proof shows that the scheme satisfies correctness and anonymity of platform identity verification. The experiment result in a devel-oped prototype system shows that the proposed scheme provides good performances in computation and communication, and is especially suitable for the wireless network.